The Socio-Economic Impact of Tourism Management on the Lives of the Community in Waterfront City Pangururan, Samosir Regency - Sepdwiyana Donargo (Journal of Economics, Management, Development, and Education, 2026)
This study aims to analyze the social and economic impacts of tourism management on the lives of the people in the Pangururan Waterfront City area, Samosir Regency. The development of this tourist area is part of the government's efforts to support the Lake Toba area as a national super priority tourism destination. The study used a qualitative descriptive approach with data collection techniques in the form of field observations, in-depth interviews, and documentation. Research informants consisted of local residents, MSMEs (Micro, Small, and Medium Enterprises), tourism managers, and tourists directly involved in tourism activities in the area. The data analysis technique used the interactive analysis model of Miles, Huberman, and Saldana through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that tourism management has a positive impact in the form of increased community income, the opening of business and employment opportunities, the development of micro, small, and medium enterprises (MSMEs), and increased social interaction between the community and tourists. However, tourism development also has negative impacts such as economic inequality, changes in community socio-cultural values, conflicts over space use, and increased pressure on the environment in tourist areas. Therefore, sustainable, participatory, and community-based tourism management is needed so that the benefits of tourism can be felt evenly while maintaining the sustainability of local culture and the environment.